Isolation and identification of indigenous Arbuscular Mycorrhizal Fungi (AMF) of forest clove rhizosphere from Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mahulette AS, Alfian A, Kilkoda KA, Lawalata IJ, Marasabessy DA, Tanasale VL, Makaruku MH. 2021. Isolation and identification of indigenous Arbuscular Mycorrhizal Fungi (AMF) of forest clove rhizosphere from Maluku, Indonesia. Biodiversitas 22: 3613-3619. Forest clove is classified as wild-type and endemic to the Maluku (Moluccas) Islands, Indonesia. The different condition of growing areas causes various types of Arbuscular Mycorrhizal Fungi (AMF) associated with forest clove. The study aimed to identify and obtain indigenous AMF inoculums from the forest clove rhizosphere from two distribution areas in Maluku. The results of AMF identification found two types of spores from the genus Glomus in the rhizosphere of forest cloves from Ambon Island with a spore density of 35/50 g of soil. In comparison, three spores were found in Seram Island, two from the genus Scutellospora and one from the Acaulospora. With an overall spore density of 5/50 g of soil. After culture trapping, there was a change in type and an increase in spore density in soil samples from the rhizosphere of the two forest clove distribution areas. Soil samples from Ambon after trapping culture obtained two new types of spores from the genus Acaulospora with a total spore number of 57/50 g soil while in soil samples from Seram found three new types of spores from the genus Glomus with a total spore count of 104/50 g of soil.